Evaluation of Crypto Assets in terms of Digital Legacy Dimension and Inheritance Tax - Burçin Bozdoğanoğlu (International Journal of Public Finance)
Internet technology, which has become an indispensable part of human life after the acceleration of the digitalisation process, shopping applications, social media accounts, cloud computing and finally cryptocurrencies with blockchain technology have opened the doors to an almost completely digital world. The footprints that individuals create and accumulate in this digital world, where they log in with their personal data to listen to music, archive photos, watch films, create e-mail accounts to follow their work and create social media accounts to communicate with their friends, have brought about the change of the concept of heritage in the traditional sense. The concept of digital heritage is a new concept in both national and international literature, the source of which is digital assets. The aim of the study is to evaluate the status of crypto assets, which cannot be categorised as money, commodity or intangible asset in our current legislation, and no new definition is made in legal and tax terms, against the inheritance transfer tax in case of acquisition and inheritance.